LITHOSTRATIGRAPHIC CHARACTERISTIC AND LITHOLOGY OF TRIASSIC-PALEOZOIC ROCKS OF SOUTHERN MANGYSHLAK - Gurbanov V.Sh. (My University, 2004)
The paper considers principles of the subdivision and correlation and a new petrographic model of Triassic–Paleozoic rocks based on their lithogenetic features. The structure of the folded basement and quasi-platform complex of southern Mangyshlak, as well as petrological–mineralogical features of Variscan granites and products of their hypergene weathering, are analyzed.
Keywords: Mangyshlak; Triassic; Paleozoic; Мезозой::Триасовая; Mesozoic::Triassic; Палеозой